1977
DOI: 10.1111/j.1365-2141.1977.tb00565.x
|View full text |Cite
|
Sign up to set email alerts
|

Factor‐VIII Activity and Antigen, Platelet Count and Biochemical Changes after Adrenoceptor Stimulation

Abstract: Adrenaline, isoprenaline and salbutamol were administered by intravenous infusion to human subjects. Isoprenaline was covered with practolol in an attempt to reduce the unpleasantness of the circulatory effects. Changes were recorded in pulse rate and blood pressure, and in blood levels of factors V, VIII, X, XI, and XII, platelet count, lactate, pyruvate, potassium and free fatty acids. Factor VIII was studied by clotting assays, by reactions with two rabbit antisera and two human antibodies, and by desulphat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

1980
1980
1989
1989

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 34 publications
3
18
0
Order By: Relevance
“…A similar relationship has been reported in normal subjects in basal condi tions, at least between F VIII:C and F VIIIR:AG [1,3,7,11,18], while there are discordant reports for F VIIIR:RCof [1,5,21], The significant correlations between the F VIII-VWF components found in our cases after VO, notwithstanding their striking and heterogeneous rise, are in agreement with previous observations made using stimuli such as catecholamine administration [7,12] and physical exercise [2,7,17], A highly significant activation of fibrino lysis was recorded following VO, the results of ELT and DBCLT being strictly correlated. This finding supports the belief that the two methods basically measure the same phe nomenon, the release of plasminogen activa tor.…”
Section: Discussionsupporting
confidence: 82%
“…A similar relationship has been reported in normal subjects in basal condi tions, at least between F VIII:C and F VIIIR:AG [1,3,7,11,18], while there are discordant reports for F VIIIR:RCof [1,5,21], The significant correlations between the F VIII-VWF components found in our cases after VO, notwithstanding their striking and heterogeneous rise, are in agreement with previous observations made using stimuli such as catecholamine administration [7,12] and physical exercise [2,7,17], A highly significant activation of fibrino lysis was recorded following VO, the results of ELT and DBCLT being strictly correlated. This finding supports the belief that the two methods basically measure the same phe nomenon, the release of plasminogen activa tor.…”
Section: Discussionsupporting
confidence: 82%
“…While long-term |3-blockade has no effect on VIII:C levels [9] the rise in VIII:C after exercise is thought to be due to |3-adrenergic stimulation [16] and can be blocked by prior intravenous administration of propranolol [32]. We have been unable to show that oral propranolol can block the rise in VIII:C with exercise, a finding also noted by KorsanBengtsen and Conradson [33], who adminis tered double the oral dose of propranolol to that used in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Since the main haemodynamic bene fits of p-blockade occur with exercise and since platelet aggregation [10][11][12][13][14] and prosta cyclin [15] have been shown to increase fol lowing acute exercise we wished to see if pblockade could alter the platelet aggregation or prostaglandin response following strenu ous exercise. In addition, since exercise-in duced release of factor VIII is thought to be mediated by p2-adrenergic stimulation [16], modification of the factor VIII complex by P-blockade was also studied. The mechanism for exercise-induced fibrinolysis is probably not related to adrenergic stimulation [ 17] but the resting level of fibrinolytic activity may be altered by P-blockade [18][19][20] and so the fibrinolytic pathway was also examined.…”
Section: Introductionmentioning
confidence: 99%
“…Venous occlusion and adrenaline infusion both produce a similar effect and it has been suggested that a good response to these challenges is desirable (Shaper et al, 1975). Factor VIII levels are also elevated by adrenaline infusion {Ingram et al, 1977) but there is no change in circulating fibrinogen level, nor is there any change in plasminogen turnover or production of fibrin(ogen) degradation products, both signs of systemic fibrinolysis (Colien and Verstraete, 1978). Our results suggest that the abrupt increase in plasma activator activity after exercise does not lead to a marked systemic fibrinolytic state; antiplasmin and plasmin ogen levels remained virtually constant but the generation of small amounts of fragment X indicates that some fibrinogenolysis was taking place.…”
Section: Discussionmentioning
confidence: 98%